Effects of friction massage of the popliteal fossa on dynamic changes in muscle oxygenation and ankle flexibility - Asakawa, Yasutsugu; Mizukami, Masafumi; Iwamoto, Koji; Ogaki, Ryo; Takemura, Masahiro; Yoshio, Masaharu (Journal of Physical Therapy Science, 2016)
[Purpose] This study aimed to examine whether or not friction massage of the popliteal fossa would be effective for achieving dynamic changes in muscle oxygenation and ankle flexibility. [Subjects and Methods] Twelve healthy male university students participated. Before and after friction massage, dynamic changes in muscle oxygenation and ankle flexibility were measured by near-infrared spectroscopy to evaluate its efficacy. [Results] Oxygenated hemoglobin was significantly higher after as compared to before massage. The range of ankle dorsiflexion tended to increase after massage. [Conclusion] These results suggest that friction massage of the popliteal fossa stimulates venous return in the lower leg.